Acetalisação da glicerina e estudo da análise conformacional dos acetais por cálculos teóricos - Viesser, Renan Vidal (2012)
This work aimed to the synthesis cis and trans isomers of the 2-phenyl-5-hydroxy-1,3-dioxane (PHD) acetal and the study of conformational equilibria by theoretical calculations. Acetals were prepared by acetalization reaction of glycerol with benzaldehyde under acidic conditions. The isomers separations were promoted by thin layer and column chromatography. In the theoretical study the initial conformations were optimized and theirs geometries were compared with the optimized structures of similar 4-phenylcyclohexanol (PCO). The potential energy surfaces (PES) were made by turn dihedral angle C7-C8-C2-O1 and C4-C5-O13-H25 by 10 in 10 degrees to 360o. The influence of substituent on conformational equilibrium were determined by inserting the groups NO2, CHO, CF3, Cl, F, CH3, OCH3, OH, NH2 and N(CH3)2 at the meta position of the aromatic ring. Studies were also performed with NBO and by atomic charges determination using Mulliken, NBO, and APT methods. Theoretical calculations were made using B3LYP method and 6-311++G(d, p) basis function. Experimental results indicated that was possible isolate the cis and trans isomers of PHD with hexane/acetone 1:1. As for the theoretical study, the optimization of the conformations showed the presence of intramolecular hydrogen bonds (IHB) OH...O between the hydroxyl hydrogen and oxygen of dioxane. It was observed the existence of unpublished IHB CH...O between the ortho hydrogen of aromatic ring and dioxane oxygen. The optimization of geometries and PES indicated a more stable conformation eqeq than axax in relation to the trans isomer of 1.04 kcal.mol-1. This is due the greater strength of IHB CH...O with the phenyl group in equatorial position. In the cis isomer the conformation eqax it was more stable than axeq by 4.29 kcal.mol-1 because of greater strength of IHB CH...O and OH...O. The influence of the substituent in the trans isomer werevery significant to reduces diaxial conformer of 15% to 1% with the NO2 group and increases to 44% with N(CH3)2 group. Finally the NBO analysis and the determination of atomic charges showed low electron density of the ortho hydrogen indicating IHB CH...O.